Multi-omics analyses reveal new insights into nutritional quality changes of alfalfa leaves during the flowering period - Liu, Yinghao; Fan, Wenqiang; Cheng, Qiming; Zhang, Lianyi; Cai, Ting; Shi, Quan; Wang, Zuo; Chang, Chun; Yin, Qiang; Jiang, Xiaowei; Jin, Ke (Frontiers in Plant Science, 2022)
High-quality alfalfa is an indispensable resource for animal husbandry and sustainable development. Its nutritional quality changes dramatically during its life cycle and, at present, no molecular mechanisms for nutrient metabolic variation in alfalfa leaves at different growth stages have been clearly reported. We have used correlation and network analyses of the alfalfa leaf metabolome, proteome, and transcriptome to explore chlorophyll, flavonoid, and amino acid content at two development stages: budding stage (BS) and full-bloom stage (FBS). A high correlation between the expression of biosynthetic genes and their metabolites revealed significant reductions in metabolite content as the plant matured from BS to FBS. l-Glutamate, the first molecule of chlorophyll biosynthesis, decreased, and the expression of HemA, which controls the transformation of glutamyl-tRNA to glutamate 1-semialdehyde, was down-regulated, leading to a reduction in leaf chlorophyll content. Flavonoids also decreased, driven at least in part by increased expression of the gene encoding CYP75B1: flavonoid 3′-monooxygenase, which catalyzes the hydroxylation of dihydroflavonols and flavonols, resulting in degradation of flavonoids. Expression of NITRILASE 2 (NIT2) and Methyltransferase B (metB), which regulate amino acid metabolism and influence the expression of genes of the glycolysis-TCA pathway, were down-regulated, causing amino acid content in alfalfa leaves to decrease at FBS. This study provides new insights into the complex regulatory network governing the content and decrease of chlorophyll, amino acids, flavonoids, and other nutrients in alfalfa leaves during maturation. These results further provide a theoretical basis for the generation of alfalfa varieties exhibiting higher nutritional quality, high-yield cultivation, and a timely harvest.